RATIONAL APPROACHES TO THE TREATMENT OF DYSLIPIDEMIA WITH DIFFERENT TOTAL CARDIOVASCULAR RISK AND ACUTE CORONARY SYNDROME - N. V. Perova; V. A. Metelskaya (Столичная издательская компания, 2015)
Approaches to the total cardiovascular risk calculation based on the actual clinical recommendations are presented as well as the application of risk categories for the choice of strategy of dyslipidemia correction. The use of statins as lipid-lowering therapy in patients with acute coronary syndrome and coronary angioplasty are also discussed.